คะแนน O-NET ภาพสะท้อนคุณภาพการศึกษาท้องถิ่น - โกมุท, วศิน (วารสารศิลปศาสตร์ มหาวิทยาลัยอุบลราชธานี, 2016)
องค์กรปกครองส่วนท้องถิ่นได้รับการถ่ายโอนสถานศึกษาจากกระทรวงศึกษาธิการในช่วงระหว่างปี 2549 – 2557 เป็นจำนวน 485 โรงเรียน ในปัจจุบันองค์กรปกครองส่วนท้องถิ่นรับผิดชอบการจัดการศึกษาตั้งแต่ระดับระดับก่อนประถมศึกษาถึงระดับประกาศนียบัตรวิชาชีพชั้นสูง โดยมีแนวโน้มจำนวนห้องเรียนและนักเรียนเพิ่มมากขึ้น ขณะที่อัตราส่วนนักเรียนต่อห้องเรียนอยู่ในเกณฑ์มาตรฐาน อย่างไรก็ตาม จากผลการทดสอบระดับชาติขั้นพื้นฐาน (O-NET) ชั้นประถมศึกษาปีที่ 6 มัธยมศึกษาปีที่ 3 และมัธยมศึกษาปีที่ 6 ที่จัดโดยสถาบันทดสอบทางการศึกษาแห่งชาตินั้น ปรากฏค่าคะแนนเฉลี่ยในทุกรายวิชาของนักเรียนในโรงเรียนสังกัดกรมส่งเสริมการปกครองส่วนท้องถิ่นต่ำกว่าค่าคะแนนเฉลี่ยระดับประเทศ ดังนั้นองค์กรปกครองส่วนท้องถิ่นจำเป็นต้องพัฒนาการจัดการศึกษาให้มีคุณภาพดียิ่งขึ้น เพื่อให้นักเรียนในสังกัดมีความรู้ไม่แตกต่างจากนักเรียนสังกัดอื่นๆ O-NET scores reflect local education quality Local governments took over the administration of 485 schools from the Ministry of Education during 2549-2557. At present, local governments are responsible for education of students of pre-school age up to the higher vocational diploma level. While the total numbers of classes and students are on the uptrend, the ratio of students per class continues to be on par with the standard. Nevertheless, the results of the Ordinary National Education Test (O-NET) for Primary Grade 6, Secondary Grade 3 and Secondary Grade 6, organised by the National Institute of Educational Testing Service, showed that the average scores in every subject of students in schools under the Department of Local Administration's jurisdiction was below the national average scores. Therefore, local governments need to improve the quality of their education administration, in order to boost the knowledge of students under their responsibilities to the same level as students under other organisations.